An ELISA-based detection of Porphyromonas gingivalis in the dental plaques of periodontal diseased patients - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
Murine hybriden:as producing lipopolisaccharides of Porphyromonas gingivalis (LPS-Pg)-specific monoclonal antibodies were established. Dental plaques were obtained from periodontal healthy subjects and patients with gingivitis or periodontitis. The levels of P. gingivalis were semiquantitatively detected by ELISA. The results showed that antibodies produced by clone Pg.C.5 were lgG2a and recognized specifically LPS-Pg, but not LPS from other periodontopathic or enteric bacteria. The presence of P. gingivalis in the dental plaque of periodontal diseased patients was able to be detected by ELISA using these antibodies. The levels of this bacterium in patients with periodontitis were much higher than those of patients with gingivitis or periodontal healthy subjects (p